Analisis Kenerja Tata Usaha Terhadap Pelayanan Guru Dan Murid di MAN INSAN CENDIKIA SORONG - Rumuar, Abdul Salam; Wahyuningrum, Sri; Rusdin (LPPM IAIN Sorong, 2022)
What we know is that administrative performance is very important in ensuring the provision of education. School administration is the spearhead of educational services in an educational institution (school). Namely as a school administrative body that directly provides internal and external services, especially to student administration. So that The aim is to determine the performance of administration in providing good, effective education to students and teachers at MAN INSAN CENDIKIA SORONG. The research method used is a descriptive approach and qualitative methods, etc. sources are selected purposively. Research data collection was carried out through observation, interviews and document study. The data obtained from this approach helps explain the results of research which aims to examine in more depth the performance of administration that provides educational services at MAN IC SORONG